Absence of a long-range ordered magnetic ground state in Pr3Rh4Sn13 studied through specific heat and inelastic neutron scattering. (12th March 2018) - Nair, Harikrishnan S; Ogunbunmi, Michael O; Ghosh, S K; Adroja, D T; Koza, M M; Guidi, T; Strydom, A M
Abstract: Signatures of absence of a long-range ordered magnetic ground state down to 0.36 K are observed in magnetic susceptibility, specific heat, thermal/electrical transport and inelastic neutron scattering data of the quasi-skutterudite compound Pr3 Rh4 Sn13 which crystallizes in the Yb3 Rh4 Sn13 -type structure with a cage-like network of Sn atoms. In this structure, Pr 3+ occupies a lattice site with D 2 d point symmetry having a ninefold degeneracy corresponding to J   =  4. The magnetic susceptibility of Pr3 Rh4 Sn13 shows only a weak temperature dependence below 10 K; otherwise remaining paramagnetic-like in the range, 10 K–300 K. From the inelastic neutron scattering intensity of Pr3 Rh4 Sn13 recorded at different temperatures, we identify excitations at 4.5(7) K, 5.42(6) K, 10.77(5) K, 27.27(5) K, 192.28(4) K and 308.33(3) K through a careful peak analysis. However, no signatures of long-range magnetic order are observed in the neutron data down to 1.5 K, which is also confirmed by the specific heat data down to 0.36 K. A broad Schottky-like peak is recovered for the magnetic part of the specific heat, C 4f, which suggests the role of crystal electric fields of Pr 3+  . A crystalline electric field model consisting of 7 levels was applied to C 4f which leads to the estimation of energy levels at 4.48(2) K, 6.94(4) K, 11.23(8) K, 27.01(5) K, 193.12(6) K and 367.30(2) K. The CEF energy levels estimated from the heat capacity analysis are in close agreement with the excitation energies seen in the neutron data. The Sommerfeld coefficient estimated from the analysis of magnetic specific heat is γ = 761 ( 6 ) mJ K −2 mol-Pr which suggests the formation of heavy itinerant quasi-particles in Pr3 Rh4 Sn13 . Combining inelastic neutron scattering results, analysis of the specific heat data down to 0.36 K, magnetic susceptibility and, electrical and thermal transport, we establish the absence of long-range ordered magnetic ground state in Pr3 Rh4 Sn13 .